Climate change stress alleviation through nature based solutions: A global perspective - Adil, Muhammad; Yao, Zijie; Zhang, Cheng; Lu, Siqi; Fu, Shenglei; Mosa, Walid F. A.; Hasan, Mohamed E.; Lu, Heli (Frontiers in Plant Science, 2022)
Global climate change stress has greatly influenced agricultural crop production which leads to the global problems such as food security. To cope with global climate change, nature based solutions (NBS) are desirable because these leads to improve our environment. Environmental stresses such as drought and salinity are big soil problems and can be eradicated by increasing soil organic matter which is directly related to soil organic carbon (SOC). SOC is one of the key components of the worldwide carbon (C) cycle. Different types of land use patterns have shown significant impacts on SOC stocks. We aim to investigate changes in various SOC fractions, including mineral associated organic carbon (MAOC), mineral associated organic matter (MAOM), soil organic carbon (SOC), easily oxidized organic carbon (EOC), microbial biomass carbon (MBC) and particulate organic carbon (POC) under various types of land use patterns (NBS), including cropping pattern, residue management, conservation tillages such as no tillage (NT) and reduced tillage (RT) using data from 97 studies on a global scale. The results showed that NT overall increased MAOC, MAOM, SOC, MBC, EOC and POC by 16.2%, 26.8%, 24.1%, 16.2%, 27.9% and 33.2% (P < 0.05) compared to CT. NTR increased MAOC, MAOM, SOC, MBC, EOC and POC by 38.0%, 29.9%, 47.5%, 33.1%, 35.7% and 49.0%, respectively, compared to CT (P < 0.05). RT overall increased MAOC, MAOM, SOC, MBC, EOC and POC by 36.8%, 14.1%, 25.8%, 25.9, 18.7% and 16.6% (P < 0.05) compared to CT. RTR increased MAOM, SOC and POC by 14.2%, 36.2% and 30.7%, respectively, compared to CT (P < 0.05). The response ratios of SOC fractions (MAOC, MAOM, SOC, MBC, EOC and POC) under NT and RT were mostly influenced by NBS such as residue management, cropping pattern, soil depth, mean annual temperature and soil texture. SOC fractions especially those taking part in driving soil biological activities, should be taken into account rather than total SOC. We emphasize the creation of site-specific management techniques for C stocks as well as the improvement of local parameterization during the creation of biogeochemical and earth system models.